Low temperature SCR of NOx over Mn/Fe mixed oxides catalyst: comparison of synthesis methods. Issue 9 (19th June 2021) - Ng, Derrick; Acharya, Durga; Wang, Xingdong; Easton, Christopher D; Wang, Jinxiu; Xie, Zongli
Abstract: BACKGROUND: With the increasing environmental pollution issues arising from NOx, the low‐temperature selective catalytic reduction (LT‐SCR) of NOx by NH3 is becoming more important. Mn/Fe mixed oxides type catalysts have been proven to be particularly effective at low temperature reactions; however, the synthesis method can be a key factor determining the SCR activities. RESULTS: A comprehensive study of LT‐SCR was carried out on a series of Mn/Fe mixed oxides catalysts prepared using diverse synthesis methods, namely, sonication assisted continuous coprecipitation (SACP), equilibrium adsorption (EA), precipitation method using either NaOH (P‐OH) or Na2 CO3 (P‐CO) as precipitant, and one pot hydrothermal synthesis (CA). The morphology, composition, crystal property, oxidation status, and surface property were systematically characterised. LT‐SCR of the NOx performance of prepared Mn/Fe catalysts was conducted in temperatures from 75 to 225 °C. It was demonstrated that, at reaction temperatures under 125 °C, LT‐SCR performance showed the trend of P‐OH > SACP > EA CA > P‐CO; meanwhile, the trend was CA > SACP > P‐OH EA > P‐CO at temperatures over 125 °C. However, N2 selectivity showed the trend SACP > CA > P‐OH overall. CONCLUSION: The characterisation results suggested that NOx conversion performance is controlled by several parameters, especially uniformity of materials, high surface area, Mn crystallinity, surface oxygen defects, Fe (III) on the surface; these are important parameters to achieve high denitrification performance as shown by P‐OH and SACP under low temperature. At higher temperatures, the stability of materials and high Brønsted acid sites on the surface are important, leading to better performance by CA and SACP.